Changes in the Authority of the Father in the Polish Family in the Twentieth Century. The Interpretation from the Historical and Pedagogical Perspective - Śpica, Paweł (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2014)
Nowadays numerous researchers are interested in the subject area concerning fatherhood, including the father’s role in bringing up the child. It is not coincidental. In the last couple of years the position of men has significantly changed in Polish families. Jerzy Witczak has indicated that since the 1970s the role of man has not been thoroughly defined. The changes have led to the modification the roles of fathers, previously which were traditionally based on taking care of material needs and representing the family to the outside world.
Keywords: father's authority; fatherhood; family upbringing